Molecular identification of sugarcane stalk rot pathogen (Phaeocytostroma sacchari) - Gopi, R; Viswanathan, R; Chandran, K; Jayaraman, Sony; Mahendran, B; Nisha, M (Journal of Sugarcane Research, 2024)
Stalk rot is one of the important diseases of sugarcane - caused by Phaeocytostroma sacchari. Survey and monitoring was done during 2020-2022 to assess the status of stalk rot in the sugarcane germplasm and molecular identiﬁcation of the associated pathogen. During the study period, 15 clones from the Saccharum officinarum recorded stalk rot incidence followed by two foreign hybrids. The clones affected were generally weak and were already affected by sugarcane bacilliform virus (SCBV). The clones 28 NG 10 and 57 NG 140 were severely affected by stalk rot. In addition, the association of Fusarium spp. was also recorded in these clones. The pathogen was studied for morphological and cultural characters and identiﬁed through molecular methods using ITS and LSU primers and in the BLAST analysis, the ampliﬁed nucleotide sequence of the pathogen shared more than 98% similarity with other already submitted nucleotide sequences of P. sacchari. As there are no reports available on the molecular identiﬁcation of this pathogen, this is the ﬁrst record of molecular identiﬁcation of P.sacchari from India.